Evaluation of cultivated gladiolus varieties of Bangladesh and radio sensitivity test for varietal improvement - Akhther, N; Islam, MR; Hassan, MK (Bangladesh Journal of Nuclear Agriculture, 2023)
The study was conducted at the research field of Nalitabari Sub-station, BINA, Sherpur during the period November 2019 to May 2020 to characterize, evaluate and select promising gladiolus varieties suitable for Bangladesh and to determine the optimum dose of radiation for LD50 for varietal improvement. The parameters studies were plant height, days to 1st flowering, number of leaves per plant, leaf length, leaf breadth, length of spike, length of rachis, number of flower per spike, flower diameter, number of corms per plant, weight of single corm, vase life, per cent germination, per cent survivability, shoot length and root length. The longest plant (154.2 cm) was observed in White Prosperity, while the shortest plant (101.7 cm) was in Regency. The longest leaf (70.3 cm) was found in Red Cascade and the shortest leaf (48.0 cm) was found in Her Majesty. The highest number of floret per spike was produced by Red Cascade (17.3) followed by White Prosperity (17.0). The Regency produced the lowest number (8.0) of floret per spike. The longest vase life (9.3 days) was observed in American Beauty followed by (8.7 days) Red Cascade, while the shortest vase life (5.7 days) was recorded in Wine and Roses. In radio sensitivity test, 30-40 Gy of gamma irradiation would be the optimal dose for inducing useful mutation in gladiolus. Bangladesh J. Nuclear Agric, 37(2): 43-56, 2023